Managing Catamenial Pneumothorax: Challenges of Diagnosis and Therapy, Literature Review - Fadel Ahmad Pratama; Russilawati Russilawati; Deddy Herman (Riviera Publishing, 2025)
Catamenial pneumothorax (CP) is a rare and recurrent spontaneous pneumothorax in women, typically occurring from 24 hours before menstruation to 72 hours afterward. While once considered uncommon, CP is now recognized in up to 30% of pneumothorax cases among women. This study aims to provide a comprehensive literature-based analysis of the etiology, diagnosis, and multidisciplinary management of CP. The research method used is a literature review that analyzes clinical cases, diagnostic imaging, histopathological findings, and treatment outcomes from various databases and published case reports. Findings suggest that while the etiology remains multifactorial—including diaphragmatic defects, lymphovascular dissemination, and hormonal influences—the use of video-assisted thoracic surgery (VATS) combined with pleurodesis and postoperative hormonal therapy (e.g., GnRH analogs) significantly reduces recurrence rates, down to 0% in some combined therapy cases. Imaging modalities like MRI during menstruation increase diagnostic accuracy. The study also underscores the importance of surgical timing, hormonal therapy continuity, and long-term monitoring for recurrence prevention. Implications of this study include the need for standardized treatment protocols and the incorporation of gynecological and thoracic collaboration in managing CP. Future research should explore biomarkers and prospective multicenter trials to refine diagnostic and therapeutic strategies.